Eddy3D: A toolkit for decoupled outdoor thermal comfort simulations in urban areas. (15th March 2022) - Kastner, Patrick; Dogan, Timur
Abstract: The architectural community needs holistic, evidence-based planning tools to promote urban resilience in the face of global warming. To ensure maximum impact, simulation-driven microclimate analysis methods must be integrated early in the design process. With Eddy3D, we present a toolkit to simulate outdoor thermal comfort metrics with a decoupled approach. We motivate the decoupled systems framework with meteorological measurements and local and global sensitivity analyses of three different climates. For a real-world case study on a university campus, we present results for both wind velocity and mean radiant temperature simulations. Finally, we discuss the advantages and disadvantages of a decoupled simulation approach that considers design aiding for the architectural practice. Our findings support reduced simulation time and flexibility, with the caveat of reduced accuracy due to neglecting forced convection, albeit this being less relevant in the early stages of design. The framework presented in this manuscript has been implemented and released as Eddy3D, a plugin for Rhino & Grasshopper. Graphical abstract: Image 1 Highlights: We introduce Eddy3D — a toolkit for decoupled outdoor thermal comfort simulation that is motivated by global sensitivity analyses. Eddy3D has been implemented as a plugin for Rhino & Grasshopper. We validated both mean radiant temperature and wind velocity simulations with on-campus, real-world measurements — and show good agreement for both. We discuss how our approach can help extract meaningful metrics such as the outdoor thermal comfort autonomy that help practitioners with performance-based decision aiding.